Material properties of random oriented pressed mat coir fibre/epoxy composites - Abdul Rahman, Mohd Amirul; Omar Baki, Munaim Ali; Mohd Rafie, Azmin Shakrine; Varatharajoo, Renuganth (Praise Worthy Prize, 2014)
The material mechanical properties of coir fibre/epoxy composite were evaluated. High increase in consumption of coconut fruit for food processing and other industrial usage nowadays lead to increase in th production of coconut trash in the form of coir fibre. These coir fibres mostly disposed as unwanted waste since there are not much further applications to utilize the coir fibres. Furthermore, the aerospace industries currently are looking for more to optimize the performance of the existing materials (e.g. metal and synthetic fibre composite) that would be introduced in aircraft structure which relatively cut the cost in production, maintenance, and in-service aircraft, eco-friendly, and low in weight factor. Therefore, natural fibre reinforce composite might be recommender answers to solve these existing problems whereby this solution already been introduced in the automotive and civil application. The existing raw coir fibres used are in the form of pressed mat and originally in the random oriented fibre form. They have been used directly in the compression moulding process together with different fibre weight ratio of 20% to 50% with epoxy resins under room temperature and controlled pressure for composite fabrication process. The fibres underwent no modification at all. Then the fabricated panels have undergone mechanical material tests; tensile, flexural and torsion test with accordance to ASTM standard to obtain mechanical properties of the material including tensile strength, tensile modulus and shear modulus. These properties data will be recorded and might be used for further analysis such as aeroelastic analysis. The results shown the composite with the higher fibre percentage being more flexible (higher tensile strength) and less than 50% of fibre loading, rigid composites were obtained.